Typology for e-business activities in the agricultural sector. (25th February 2008) - Andreopoulou, Z.; Tsekouropoulos, G.; Koutroumanidis, T.; Vlachopoulou, M.; , B. Manos
The internet constitutes an effective business resource as it provides a persistent communication infrastructure as well as huge business opportunities and information capital worldwide. The aim of this paper is to create a typology for e-business activities in the agricultural sector. The methodology concerns the study of the principles of e-business and its practice in the agricultural sector, the examination of the existing e-business models on the internet and, furthermore, the study of the websites promoting e-business in agriculture, their classification under the existing models and their evaluation through a multicriteria method. As a case study to apply the methodology described, the agricultural business sector in Greece is selected. Regarding classification, enterprises in the e-agricultural sector are classified according to the stage of the 'interaction', where beyond mere presence on the internet, there is a possibility for the user to navigate through the website and collect numerous information.